Italian crime filmography, 1968-1980 - Curti, Roberto, 1971- (McFarland & Company, Inc., Publishers, 2013)
"In 1970s Italy, crime films were the most popular, profitable and controversial genre. The product of a country plagued with violence, political tensions and armed struggle, these films managed to capture and convey the widespread anxiety and anger in their tales. This book includes all the crime films produced in Italy between 1968 and 1980"--